Pyrotinib promotes the antitumor effect of T-DM1 by increasing drug endocytosis in HER2-positive breast cancer - Wenjun Ren; Tienian Zhu; Jiankun Liu; Ruijing Zhao; Fei Zhao; Yimei Zhang; Jianping Mu (Scientific Reports)
Abstract Anti-HER2 therapy is integral to the treatment of HER2-positive breast cancer, but drug resistance hampers its effectiveness. Although antibody-drug conjugates (ADCs) are increasingly used in clinical practice, their application is often hindered by adverse reactions and drug resistance. Therefore, it is crucial to enhance the bioavailability of ADCs and reduce their dosages to mitigate both adverse effects and resistance. Pyrotinib’s effect on HER2-positive breast cancer cell lines (SK-BR-3 and JIMT-1) was investigated via western blot, focusing on HER2 and downstream pathways. Pyrotinib’s influence on HER2 ubiquitination and internalization was assessed through RT-qPCR, western blot, and immunofluorescence. The ability of pyrotinib to augment trastuzumab emtansine (T-DM1) endocytosis and antiproliferative effects was studied via CCK-8 and immunofluorescence. In vivo experiments in nude mice were conducted to explore the therapeutic efficacy of T-DM1 combined with pyrotinib. The single-drug study showed that pyrotinib downregulated HER2 protein levels and HER2 downstream signaling pathways. The mechanism of downregulating HER2 protein levels involved the promotion of HER2 internalization and degradation through the ubiquitin-proteasome pathway. The two-drug combination study showed that pyrotinib promoted the endocytosis of T-DM1, which improved its bioavailability. Increased cellular uptake further enhanced the antitumor effects of T-DM1 in both in vitro and in vivo experiments. Our results reveal the molecular mechanism by which pyrotinib regulates HER2 levels by promoting HER2 internalization, thereby facilitating the endocytosis of T-DM1. These findings suggest a potential combination treatment strategy for the targeted therapy of HER2-positive breast cancer.